THE USE OF TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION: DIGITAL INCLUSION IN THE SOCIETY 5.0 ERA - Alya Kamilin; Muhammad Solekhin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
In the world of education, technology is very influential in facilitating all educational activities. The existence of this educational technology can maximize the teaching and learning process, besides that technology can also be called a complement in teaching and learning activities. The presence of technology in Islamic Religious Education learning also enriches a more flexible learning experience. Learning is no longer limited to formal classrooms, but can be done anytime and anywhere. The research method used in this study is qualitative research with a case study approach. A case study is an exploration of "a bound system" or "various cases" which from time to time through in-depth data collection and involves various sources of rich information in a context. The main sources used as references are e-books, journals, and similar literature. The results of writing this article Technology as a very powerful tool must be used wisely so that it is in line with Islamic principles that emphasize justice, honesty, responsibility and benefits for humans. The Society 5.0 era provides many opportunities to improve Islamic religious education through digital platforms. For example, distance learning provides access to quality education for those in remote areas. Mobile learning allows learning anytime with a smartphone application, while MOOCs provide free online courses from well-known institutions. Digital libraries facilitate access to Islamic literature, and streaming lectures spread the knowledge of scholars to a wide audience